Pengembangan Desa Wisata Berbasis Kearifan Lokal - Neneng Komariah; Encang Saepudin; Pawit M. Yusup (Universitas Merdeka Malang, 2018)
The area of ​​Paledah Village, Padaherang District, Pangandaran Regency is very potential to be developed. This village has interesting natural characteristics, unique social and cultural life. This potential must be encouraged and developed in accordance with the socio-cultural characteristics of the community. The development of community-based tourism is a strategic effort to build the community. Rural tourism development is a long-term and potential investment for the government because human resources and natural resources are available. The purpose of this study was to find out the development of tourism villages based on local wisdom, especially related to the concept of criteria for tourism villages in Paledah village. This study uses a qualitative approach. The process of collecting data used were interviews, observation, Forum Group Discussion (FGD), and literature review. The data analysis technique in this study was descriptive with the stages of data reduction and presentation as well as composing the conclusions. Validity and reliability tests were carried out through a triangulation process. The informants in this study were the government, tourism village communities, and tourism developers which totally 9 (nine) people. The results of the study indicate that the values ​​of local wisdom in the development of agro tourism villages in Pangandaran Regency are contained in organizational principles. There are three main principles of organization, namely voluntary and opened-membership, democracy-based management, and independence. Village tourism criteria include attraction, accessibility, public facilities and tourist facilities, community empowerment, and marketing or promotion. Based of the five criteria for tourism villages in Paledah village, only two that have been running optimally, namely tourist attraction and community empowerment, while the other three criteria still have problems.